Advances in library administration and organization. Vol. 28 - Nyce, James M.; Golden, Janine; Williams, Delmus Eugene; Emerald eBooks (Bingley, U.K. : Emerald, 2009)
The Advances in Library Administration and Organization Series seeks to develop a body of research literature that contributes to the base of organizational theory upon which library administrators rely. Its mix of contributions to the literature of library administration and organization is intended to be both diverse and eclectic. The volume 28 provides a collection of thought-provoking articles on issues relating to problems library managers face and strategies in addressing those challenges. The topics covered in this volume include: managing change in research libraries; the agility of library consortia and its member libraries; the evaluation of reference services; developing a recruitment strategy for a diverse workforce; the evaluation of training and professional development programs; and, collective bargaining within faculty unions on college campuses. Advances is widely read by practitioners, library and information science graduate students, and those working in associated fields of information management, and remains the premier series in its area of coverage. This latest volume adds another significant contribution to the literature of library and information centre management.
Librarians and the complexity of individual and organizational change : case study findings of an emergent research library / Donald L. Gilstrap -- Why librarianship? : an exploration of the motivations of ethnic minorities to choose library and information science as a career / Lisa K. Hussey -- An unrelenting need for training / Barbara J. Stites -- Library faculty and collective bargaining : an exploration / Stephen H. Aby -- Work in motion/assessment at rest : an attitudinal study of academic reference librarians a case study at mid-size university (MSU A) / Bella Karr Gerlich -- An exploratory case study of leadership for organizational agility in a consortium of small private college libraries / Jean K. Mulhern -- Consortia activity in academic libraries : anti-competitive or in the public good? / Catherine Maskell -- Introduction / Delmus E. Williams.
Includes index.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General; Library, archive & information management; Library administration; Electronic books